The Influence of UNIMED Management Lecturers' Skills in Teaching and Discipline on UNIMED Management Students' Satisfaction - Rizkillah, Ridho; Sinaga, Mhd. Fadillah Ilham; Kodratullah, Muhammad Lintar; Julian, T. Rendy; Simanjuntak, Julius Wisesha; Siregar, Zulkarnain (Economic: Journal Economic and Business, 2024)
In an era where education is increasingly developing rapidly, a number of programs from the government have changed the learning system in daily lectures, where the role of lecturers is often required to be the spearhead in attracting students' interest in learning. Lecturers are given the freedom to choose the best learning methods, strategies and techniques according to their needs. courses, students, teachers, and circumstances. teaching ability to produce innovative and effective learning. In this case, a teacher must be able to innovate in teaching activities so that students can feel satisfaction during the learning process. This research aims to fill this knowledge gap by studying the Influence of Teaching Ability and Lecturer Discipline on Student Learning Satisfaction (Case Study in the Department of Management, Medan State University). This research uses quantitative methods. The data collection technique used in this research is a questionnaire. The population in the study were students majoring in Management at Medan State University.